2011
DOI: 10.1088/0004-637x/728/2/77
|View full text |Cite
|
Sign up to set email alerts
|

RADIO AND Γ-Ray CONSTRAINTS ON THE EMISSION GEOMETRY AND BIRTHPLACE OF PSR J2043+2740

Abstract: We report on the first year of Fermi γ-ray observations of pulsed high-energy emission from the old PSR J2043 + 2740. The study of the γ-ray efficiency of such old pulsars gives us an insight into the evolution of pulsars' ability to emit in γ rays as they age. The γ-ray light curve of this pulsar above 0.1 GeV is clearly defined by two sharp peaks, 0.353 ± 0.035 periods apart. We have combined the γ-ray profile characteristics of PSR J2043 + 2740 with the geometrical properties of the pulsar's radio emission,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Figure 2 also exhibits a decrease in the ratio of peaks P1 and P2 with increasing energy. Also observed in other LAT pulsars (see, e.g., Abdo et al 2010cAbdo et al , 2010dNoutsos et al 2011), this is thought to be caused by varying gamma-ray emission altitudes and curvature radii of the magnetic field lines as the pulsar rotates (Abdo et al 2010d).…”
Section: Pulse Profile and Spectral Parametersmentioning
confidence: 77%
“…Figure 2 also exhibits a decrease in the ratio of peaks P1 and P2 with increasing energy. Also observed in other LAT pulsars (see, e.g., Abdo et al 2010cAbdo et al , 2010dNoutsos et al 2011), this is thought to be caused by varying gamma-ray emission altitudes and curvature radii of the magnetic field lines as the pulsar rotates (Abdo et al 2010d).…”
Section: Pulse Profile and Spectral Parametersmentioning
confidence: 77%
“…PSR J2043+2740 (Ps=0.096 s) is a radio loud (Ray et al 1996) γ-ray pulsar (Pellizzoni et al 2009;Abdo et al 2010;Noutsos et al 2011). Its X-ray counterpart was detected by XMM-Newton but no X-ray pulsations were detected (Becker et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Pulsed GeV γ-ray emission from more than 100 pulsars 10 has been observed by the Large Area Telescope (LAT; Atwood et al 2009) aboard the Fermi satellite, launched in 2008 June (see The Second Fermi Large Area Catalog of Gamma-Ray Pulsars; Fermi LAT Collaboration 2013, hereafter 2PC). The current population of γ-ray pulsars includes objects known from independent radio or X-ray observations and detected in γ rays by folding the Fermi LAT data at the known rotational periods (e.g., Abdo et al 2009a;Noutsos et al 2011;Espinoza et al 2013), and γ-ray pulsars found through direct blind searches of the LAT data (Abdo et al 2009b;Pletsch et al 2012) or radio searches for pulsars in unassociated γ-ray sources (see Ray et al 2012, and references therein). These pulsars are energetic (spindown luminositiesĖ = 4π 2 IṖ/P 3 > 10 33 erg s −1 , where P is the spin period,Ṗ is its first time derivative, and I denotes the moment of inertia, assumed to be 10 45 g cm 2 in this work) and are typically nearby.…”
Section: Introductionmentioning
confidence: 99%